Primerjava postopkov priznanja in izvršitve po Newyorški konvenciji in Bruseljski uredbi Ia - Polajžar, Aljoša (Podjetje in delo, 2021)
The article compares the systems of recognition and enforcement of court judgments and arbitral awards under the New York Convention (NYC) and the Brussels Ia Regulation (Regulation 1215/2012). We focus on the reasons for refusing recognition and enforcement, and on the analysis of the strengths and weaknesses of both systems. Based on the comparative analysis, we conclude that both instruments promote cross-border enforcement and recognition of decisions. This is evident in the narrow explanation of reasons for refusing recognition and enforcement, and the low number of cases in which refusal is successful. Furthermore, we conclude that Regulation 1215/2012 provides a good example for consideration of further removal of language barriers (requirements for arbitral award translation into the official language of the executing state) under the NYC on the global level. Finally, we propose to consider the abolition of exequatur (following the example of Regulation 1215/2012) under the NYC. An obstacle to this step, however, is the legal limitation of the principle of mutual trust - which is the conceptual basis for the abolition of exequatur - only to the Member States of the European Union.
Keywords: arbitral award; arbitražna razsodba; Bruseljska uredba Ia; Brussels Ia Regulation; eksekvatura; exequatur; international commercial arbitration; jezikovne ovire; linguistic barriers; mednarodna gospodarska arbitraža; mutual trust; načelo medsebojnega zaupanja; New York Convention; Newyorška konvencija; priznanje in izvršitev; recognition and enforcement